2019
DOI: 10.3390/min9080468
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical Characterization of Iron and Steel Slag and Its Potential to Remove Phosphate and Neutralize Acid

Abstract: Iron and steel slags from legacy and modern operations in the Chicago-Gary area of Illinois and Indiana, USA, are predominantly composed of Ca (10–44 wt. % CaO), Fe (0.3–28 wt. % FeO), and Si (10–44 wt. % SiO2), with generally lesser amounts of Al (<1–15 wt. % Al2O3), Mg (2–11 wt. % MgO), and Mn (0.3–9 wt. % MnO). Mineralogy is dominated by Ca ± Mg ± Al silicates, Fe ± Ca oxides, Ca-carbonates, and high-temperature SiO2 phases. Chromium and Mn concentrations in most samples may be environmentally significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…The nonferrous slag includes copper slag, zinc slag, lead-zinc slag, and nickel slag. Several studies highlighted the importance of reprocessing waste piles for secondary metal recovery, thus, generating revenues [64,65]. Of course, one of the keys issues to be addressed is that the slag is generally characterized by an uneven distribution of the target components throughout the slag dump [66].…”
Section: Co-occurrence Keyword Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…The nonferrous slag includes copper slag, zinc slag, lead-zinc slag, and nickel slag. Several studies highlighted the importance of reprocessing waste piles for secondary metal recovery, thus, generating revenues [64,65]. Of course, one of the keys issues to be addressed is that the slag is generally characterized by an uneven distribution of the target components throughout the slag dump [66].…”
Section: Co-occurrence Keyword Networkmentioning
confidence: 99%
“…However, the laboratory tests performed by Kasikow et al demonstrated that a recovery process for large volumes of nickel-cobalt technogenic raw materials is valid to the total volume of slag [66]. On the other hand, bio-assisted extraction of metals from historical slag by use of Acidithiobacillus thiooxidans was demonstrated as being technical feasible and, at the same time, economically efficient [65]. Another already in practice example of metal recovery is the modern smelter of Zambian Copperbelt where the historical copper tailing was revisited for extraction of cobalt recovery [64].…”
Section: Co-occurrence Keyword Networkmentioning
confidence: 99%
“…The slag can be characterized using Xray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy with energy-dispersive spectrometry (SEM-EDS), and light optical microscopy (LOM) in transmitted and reflected light [45][46][47]. Previous studies have indicated that copper slag behaves differently when subjected to different temperatures, thus exhibiting different properties [42,48]. BCL slag was characterized to analyze its composition.…”
Section: Uses Of Metallurgical Slagmentioning
confidence: 99%
“…Direct reduction is one method used to recover iron from the slag by reducing Fe 3 O 3 and Fe 2 SiO 4 found in copper slag to metallic iron using coal. This involves using reduction temperatures of about 1300 • C over the course of 30 min, giving an output of 98.13% Fe [48]. Iron is a vital metal element that encourages the growth of humanity and national economies [62,63].…”
Section: Reuse and Recycling Of Copper Slagmentioning
confidence: 99%
“…Another example of how to reuse metallurgical slags is presented in the contribution of Piatak et al [7]. Through the study of ferrous slags from the Chicago-Gary area (Illinois and Indiana, USA), the effective removal of phosphates from solution was documented.…”
mentioning
confidence: 99%